Critical success factors of temporary retail activations: A multi-actor perspective. (January 2018) - Lowe, Jennifer; Maggioni, Isabella; Sands, Sean
Abstract: Temporary retail activations have been increasingly adopted by brands as an innovative experiential marketing strategy to engage existing and new customers. Through a series of in-depth interviews with multiple-actors (agency executives, brand managers, and consumers), this study identifies divergences and commonalities in defining the concept of temporary retail activation success. Further, we propose a conceptual framework of key factors that can contribute to the success of experiential-driven initiatives in retail. Four critical success factors (relational touchpoint, strategic alignment, surprise and delight, and serendipity) are discussed. We suggest that temporary retail activations should be considered as retail exchange events aimed at generating relationship-driven outcomes.